Avaliação de emulsões fotoprotetoras do tipo O/A produzidas com óleo de babaçu (Orbignya phalerata) - Chaves, Raiane Vieira (2021)
The incidence of the sun's ultraviolet (UV) rays on the skin, without proper protection, can cause the appearance of endemas, erythema, melasma and even skin cancer, making the use of sunscreens indispensable. Thus, the work aimed to evaluate the photoprotection capacity of cosmetic emulsions produced with oil extracted from babassu seeds (Orbignya phalerata). The determination of volatile compounds in the oil was performed by chromatography (CG-MS), identifying the presence of lauric acid and myristic acid as predominant compounds. The antioxidant activity evaluated was 863,80 µg mL-1 (IC50), 0,099 (IAA) and 29,53% chelating ability. The oil had a total phenol concentration of 19,93 mg EAG g-1 of oil and a sun protection factor (SPF) of 1,42. In the construction of the pseudo-ternary phase diagram, specific proportions of babassu oil (oily phase), Milli-Q water (aqueous phase), Procetyl (surfactant) and oleic acid (cosurfactant) in a 2:1 ratio were used. The obtained emulsions presented oil-inwater (O/W) emulsion characteristics and pseudoplastic fluid behavior, according to the flow curve by rheological analysis, allowing better spread and coverage of the skin. Emulsions prepared with 5% oil in their formulation showed average sun protection capacity with SPF of 22,54, 20,00 and 18,72. Therefore, the use of babassu seed oil showed potential for the production of photoprotective emulsions.